Atypical 7q11.23 deletions excluding ELN gene result in Williams–Beuren syndrome craniofacial features and neurocognitive profile. Issue 1 (24th October 2020) - Alesi, Viola; Loddo, Sara; Orlando, Valeria; Genovese, Silvia; Di Tommaso, Silvia; Liambo, Maria Teresa; Pompili, Daniele; Ferretti, Daniele; Calacci, Chiara; Catino, Giorgia; Falasca, Roberto; Dentici, Maria Lisa; et al.
Abstract: Williams–Beurens syndrome (WBS) is a rare genetic disorder caused by a recurrent 7q11.23 microdeletion. Clinical characteristics include typical facial dysmorphisms, weakness of connective tissue, short stature, mild to moderate intellectual disability and distinct behavioral phenotype. Cardiovascular diseases are common due to haploinsufficiency of ELN gene. A few cases of larger or smaller deletions have been reported spanning towards the centromeric or the telomeric regions, most of which included ELN gene. We report on three patients from two unrelated families, presenting with distinctive WBS features, harboring an atypical distal deletion excluding ELN gene. Our study supports a critical role of CLIP2, GTF2IRD1, and GTF2I gene in the WBS neurobehavioral profile and in craniofacial features, highlights a possible role of HIP1 in the autism spectrum disorder, and delineates a subgroup of WBS individuals with an atypical distal deletion not associated to an increased risk of cardiovascular defects.